A mini smart solar driven hydrogen production process with chemical looping reforming for microgrids. (July 2018) - Jiang, Qiongqiong; Zhang, Hao; Kang, Qilan; Hong, Hui; Jin, Hongguang
Abstract: Solar thermochemical production of hydrogen with methane reforming is a primary and appropriate strategy for a mini smart electricity system. Importantly, perovskite-type materials are state-of-the-art oxygen carriers (OCs) for solar methane reforming systems with hydrogen production and storage which exhibit thermal stability and prior physicochemical properties. A series of LaCux Ni1-x O3 materials are prepared by combustion methods and tested via BET, XRD, SEM and TGA. The redox performance of the LaCux Ni1-x O3 under different reducing and oxidizing atmospheres are discussed using thermogravimetric analysis. It is demonstrated that copper substitution facilitates the release of oxygen and the production of hydrogen along with solar-to-fuel efficiency.